Community structure and association network of prokaryotic community in surface sediments from the Bering-Chukchi shelf and adjacent sea areas - Xie, Changliang; Ouyang, Hong; Zheng, Hu; Wang, Maoting; Gu, Junning; Wang, Zhaohui; Tang, Yali; Xiao, Lijuan (Frontiers in Microbiology, 2024)
The Bering-Chukchi shelf is one of the world's most productive areas and characterized by high benthic biomass. Sedimentary microbial communities play a crucial role in the remineralization of organic matter and associated biogeochemical cycles, reflecting both short-term changes in the environment and more consistent long-term environmental characteristics in a given habitat. In order to get a better understanding of the community structure of sediment-associated prokaryotes, surface sediments were collected from 26 stations in the Bering-Chukchi shelf and adjacent northern deep seas in this study. Prokaryote community structures were analyzed by metabarcoding of the 16S rRNA gene, and potential interactions among prokaryotic groups were analyzed by co-occurrence networks. Relationships between the prokaryote community and environmental factors were assessed. Gammaproteobacteria, Alphaproteobacteria, and Flavobacteriia were the dominant bacterial classes, contributing 35.0%, 18.9%, and 17.3% of the bacterial reads, respectively. The phototrophic cyanobacteria accounted for 2.7% of the DNA reads and occurred more abundantly in the Bering-Chukchi shelf. Prokaryotic community assemblages were different in the northern deep seas compared to the Bering-Chukchi shelf, represented by the lowered diversity and the increased abundant operational Taxonomic Units (OTU), suggesting that the abundant taxa may play more important roles in the northern deep seas. Correlation analysis showed that latitude, water depth, and nutrients were important factors affecting the prokaryote community structure. Abundant OTUs were distributed widely in the study area. The complex association networks indicated a stable microbial community structure in the study area. The high positive interactions (81.8%-97.7%) in this study suggested that symbiotic and/or cooperative relationships accounted for a dominant proportion of the microbial networks. However, the dominant taxa were generally located at the edge of the co-occurrence networks rather than in the major modules. Most of the keystone OTUs were intermediately abundant OTUs with relative reads between 0.01% and 1%, suggesting that taxa with moderate biomass might have considerable impacts on the structure and function of the microbial community. This study enriched the understanding of prokaryotic community in surface sediments from the Bering-Chukchi shelf and adjacent sea areas.